2016
DOI: 10.1096/fj.201500194r
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress disassembles the p38/NPM/PP2A complex, which leads to modulation of nucleophosmin‐mediated signaling to DNA damage response

Abstract: Oxidative stress is a leading cause of endothelial dysfunction. The p38 MAPK pathway plays a determinant role in allowing cells to cope with oxidative stress and is tightly regulated by a balanced interaction between p38 protein and its interacting partners. By using a proteomic approach, we identified nucleophosmin (NPM) as a new partner of p38 in HUVECs. Coimmunoprecipitation and microscopic analyses confirmed the existence of a cytosolic nucleophosmin (NPM)/p38 interaction in basal condition. Oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…We found that upregulation of p38β, but not p38α, is a common event in AML cases that contributes to the SET-dependent inactivation of PP2A in AML, pointing to a relevant role of p38β in this aggressive disease. It has been reported that PP2A can regulate p38 signaling pathway, and that PP2A and p38 form complexes in the cytoplasm in basal conditions; in fact, p38 may act as scaffold protein for NMP and PP2A [42][43][44][45] . However, the nature of their connection varies depending on the context.…”
Section: Discussionmentioning
confidence: 99%
“…We found that upregulation of p38β, but not p38α, is a common event in AML cases that contributes to the SET-dependent inactivation of PP2A in AML, pointing to a relevant role of p38β in this aggressive disease. It has been reported that PP2A can regulate p38 signaling pathway, and that PP2A and p38 form complexes in the cytoplasm in basal conditions; in fact, p38 may act as scaffold protein for NMP and PP2A [42][43][44][45] . However, the nature of their connection varies depending on the context.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the role of PP2a in deactivation of p38 remains cell type- and stimuli-dependent. Indeed, inhibition of PP2A in endothelial cells is associated with increased phosphorylation of p38 in unstimulated cells but does not affect oxidative stress-induced p38 activation [ 56 ]. Interestingly, in endothelial cells, MAP kinase phosphatase-1 (MKP-1) is also a negative regulator of p38 activity and p38-dependant VCAM expression in response to shear stress [ 57 ].…”
Section: The P38 Pathwaysmentioning
confidence: 99%
“…Endogenous ROS are mainly produced by the mitochondrial respiratory chain and also by enzymatic reactions involving NADPH oxidase (NOX), xanthine oxidase, nitric oxide synthase (NOS), arachidonic acid, and metabolizing enzymes such as the cytochrome P450 enzymes, lipoxygenase, and cyclooxygenase [ 103 ]. Exogenous sources of ROS are generated mainly by ionizing radiation, UV, xenobiotics and pollutants [ 56 ].…”
Section: The P38 Pathway As a Major Regulator Of The Oxidative Stressmentioning
confidence: 99%
“…P38MAPK also functions to control proliferation, differentiation, and migration of endothelial cells. A recent study revealed that as a newly discovered partner of p38 in HUVECs, nucleophosmin (NPM) impairs DNA damage response [15]. …”
Section: Signaling Pathways Involved In Oxidative Stressmentioning
confidence: 99%